Efficacy of Nano Biochar Coated Urea in Enhancing Soybean Growth and Yield - Hariyono; Putra, Anggi Rama; Mulyono; Isnawan, Bambang Heri (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
One agricultural product with significant economic worth is soybeans. In Indonesia, soybean production is still low, while demand is high. Soybean productivity on coastal sandland can be increased by increasing the effectiveness of fertilizer with the use of nano biochar-coated urea fertilizer. This investigation seeks to evaluate the efficacy of nano-biochar coatings applied to various forms of urea as a nitrogen slow-release mechanism to enhance the growth and yield of soybean crops in coastal sandy terrain. This empirical research was executed within the Agricultural Experiment Greenhouse at Muhammadiyah University of Yogyakarta from March to June 2022. The methodology employed was experimental research utilizing a single-factor design organized according to a Completely Randomized Design (CRD) comprising six treatments. Each treatment included six plant samples with three replications, specifically: Urea Prill, Nano Biochar Coated Urea Prill, Urea Granules, Nano Biochar Coated Urea Granules, Urea Tablet, and Nano Biochar Coated Urea Tablet. The findings indicated that applying nano-biochar derived from coconut shells to urea prill significantly promotes the growth and yield of soybeans within coastal sandy soil. In future agronomic applications, nano biochar-coated urea prill can enhance urea's efficacy and improve soybean yields. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 6: Clean Water and Sanitation SDG 13: Climate Action SDG 15: Life on Land